Can worker codetermination stabilize democracies? Works councils and satisfaction with democracy in Germany - Christian Pfeifer (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2023)
Many citizens are relatively dissatisfied with the democratic regimes they live in, which can be a threat to political stability. This paper reports empirical evidence that workers in firms with works councils are on average significantly more satisfied with the democracy as it exists in Germany than workers in firms without such a participatory workplace institution. This result holds in regressions for subsamples, in panel regressions accounting for unobserved individual heterogeneity, and in endogenous treatment regressions. It gives support to the "spillover thesis" that participatory workplace characteristics have a broader effect on society. Consequently, strengthening worker codetermination might help to increase the overall satisfaction with the democratic regime and foster political stability.
Keywords: D02; D72; J58; J83; 330; democracy; codetermination; satisfaction; "spillover thesis"; works councils